Analisis Hubungan Faktor Pekerjaan terhadap Substandard Action pada Pekerja Divisi Fabrikasi PT X - Ningtiyas, Shinta Feby; Ernawati, Meirina; Al-Furqony, Muhamad Isa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Work accidents are unplanned, uncontrolled and unwanted events that can be caused by substandard actions at work. Substandard action is defined as individual action that has the potential to cause work accidents. This research aims to see the relationship between work factors (supervision and availability of workers' PPE) on substandard action. The research method uses a quantitative approach with a cross sectional study design. The population of this study was all 30 employees of PT X's fabrication division. Meanwhile, the research sample uses a total population technique, which means that the research sample is all 30 workers in the fabrication division. Data collection uses primary data by filling out questionnaires on supervision variables, availability of PPE, and substandard action. In addition, data collection also uses secondary data in the form of company profiles and work accident data. Data calculations are assisted by the SPSS 21 application through the contingency coefficient test (c). The research results show that there is a significant relationship between the supervision variable and substandard action with a coefficient value of 0.503. Apart from that, the research results also show that there is a weak relationship between the variable availability of worker PPE and substandard action with a coefficient value of 0.137. Job factors have an influence on workers' substandard actions. Supervision is a benchmark for taking action that can support the expected achievements. Lack of supervision can be a cause of work accidents. Apart from that, the availability of PPE is also an important thing to pay attention to to maintain the health and safety of workers. If the availability of PPE for workers is not optimal, work accidents will occur.